A Comparative Study on Effect of Motivation and Hope on the Well-being of Geriatric Population - Apoorva Sharma1 , Shikha Srivastava2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: For the last decade, the physical and the mental health has been the concern and most interestamong the researchers. This relationship is most discussed among geriatric population, because of thevarious challenge’s posed by the old age at various levels. Here in this study we have how motivation andhope enhances the living wellbeing.Aim: To measure the effect of motivation level, hope and well-being of geriatric populationMethodology: The present study was conducted in Delhi – NCR societies. Overall sample size of the studywas 60 elderly population both male and female. Hypertension elderly (n =30) and Healthy elderly (n =30).The study was conducted using Elderly Motivational Scale, Adult Hope Scale and Ryffs Psychological WellBeing Scale.Conclusion: The well-being of hypertension group (experimental group) is at a higher side than healthyelderly group (control group).